2018
DOI: 10.3390/f9100607
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Vegetation Responses to Invasive Shrub Control Techniques for Amur Honeysuckle (Lonicera maackii [Rupr.] Herder)

Abstract: Invasive shrubs in forest understories threaten biodiversity and forest regeneration in the eastern United States. Controlling these extensive monotypic shrub thickets is a protracted process that slows the restoration of degraded forest land. Invasive shrub removal can be accelerated by using forestry mulching heads, but evidence from the western United States indicates that mulching heads can promote exotic species establishment and mulch deposition can reduce native plant species abundance. We compared the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Some other, less closely related forest invaders have been considered in forestry mower studies, however. For example, Lonicera maackii and Alliaria petiolata have both been shown to be stimulated following shallow forestry mowing with more negative impacts on L. maackii accruing with deeper forestry mowing (Frank et al ), but this is largely a function of disturbance caused by the forestry mower itself—something not included in our experimental design—and not the depth of resulting mulch. We speculate that mechanisms similar to the ones that led to our results would lead to comparable effects in other species, but this remains to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Some other, less closely related forest invaders have been considered in forestry mower studies, however. For example, Lonicera maackii and Alliaria petiolata have both been shown to be stimulated following shallow forestry mowing with more negative impacts on L. maackii accruing with deeper forestry mowing (Frank et al ), but this is largely a function of disturbance caused by the forestry mower itself—something not included in our experimental design—and not the depth of resulting mulch. We speculate that mechanisms similar to the ones that led to our results would lead to comparable effects in other species, but this remains to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…However, without follow‐up treatment, the cover of barberry rebounded 40% in 5 years. Frank et al (2018) observed a similar rebound in the cover of L. maackii two‐years following mastication without follow‐up treatments. Maintaining goats on our treatment sites over the 5‐year study prevented a similar recovery of invasive shrubs.…”
Section: Discussionmentioning
confidence: 84%
“…Reductions in invasive shrubs increase the availability of light in forest understories (Owings et al 2017), which allows the establishment of less shade‐tolerant species. In addition, the herbaceous flora of most forests in the region consists of resilient species that experienced a historic filter of anthropogenic disturbance, including grazing by livestock (Frank et al 2018). Therefore, grazing‐sensitive species may not be present in the seedbanks of many contemporary forests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of treatment techniques are used to control invasions of L. maackii (as well as many other woody shrubs); all are included in at least one of the following four categories: physical, biological, cultural, and chemical (Radosevich et al 1997). Physical removal includes manual techniques such as root wrenching, lopping, or root severing (Oneto et al 2010), as well as mechanical removal in the form of brush-cutting and mulching-head treatments (Frank et al 2018). While these methods may disturb the substrate, they are generally considered to be more environmentally safe and can be relatively inexpensive to apply but may require more work hours than other treatments (Bailey et al 2011), and some manual techniques require access to specialized equipment (Frank et al 2018;Oneto et al 2010).…”
Section: Introductionmentioning
confidence: 99%